The Influence of Future Time Perspective on Registered Nurses’ Behaviors toward Delegation, and Thriving at Work - amal H. Abou Ramdan (Evidence-Based Nursing Research)
Context: Nurses with a high future time perspective talented at setting a goal in the distant future and make every effort to achieve through developing their plan and priorities tasks.